Student’s perception on UMS science foundation programme in developing their knowledge and skills for engineering courses - Sitty Nur Syafa Bakri; Nurliyana Juhan; Che Haziqah Che Husin; Ayu Afiqah Nasrullah (Global Academic Excellence (M) Sdn Bhd, 2022)
Since its accreditation by MQA in 2018, the UMS Foundation in Science Program, through PPST has continuously produced high quality standards for students furthering their studies in UMS. Clinging to its accredited program means that quality assurance of foundation’s teaching and learning will be maintained and monitored. Herein, this study reports the feedback given by the foundation program’s alumni whose continue in undergraduate study of UMS Engineering. The objective is to investigate the students’ perception on knowledge and skills they obtained throughout the foundation year in relation to their courses study. A questionnaire with open ended question was constructed through a google form and designed in accordance with the MQA program review and monitoring guideline with 4 Likert scale (1- strongly disagree, 2- disagree, 3-agree and 4-strongly agree). Among 35 student’s replies, almost everyone answered high percentage of number 3 and 4, indicating an agreement towards knowledge and skills aspects. 100% student agree that the foundation program give them new knowledge and strengthen the basic theories in their engineering courses. Meanwhile, 94% believed that the foundation courses strengthen the personal skills, contribute to the achievement in engineering course and assist them to apply the skills obtained in foundation for lifelong learning. In open-ended questions, two themes of answers: (i) strength; (ii) hopes and expectations were organized, which highly in line with the students’ feedback in the Likert scale scores. This is in accordance with the student agreement that Foundation in Science Programme of UMS does provide basic knowledge and skills that relevant to the Engineering course in UMS. Further suggestions received and changes to the programme in the new academic year will be continuously monitored and reviewed for academic quality assurance.